2001
DOI: 10.1055/s-2001-14072
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of Coagulation/Fibrinolysis Parameters for the Termination of Pregnancy Complicated by Severe Preeclampsia

Abstract: We investigated coagulation/fibrinolysis parameters for significant differences between patients with early-onset severe preeclampsia (< 32 weeks gestation, wG) and those with late-onset severe preeclampsia (Ն 32 wG). A decrease in antithrombin (AT), protein C (PC), and free protein S (PS) activities and an increase in plasmin-␣2-plasmin inhibitor complex (PIC), thrombin-antithrombin complex (TAT), and FDP D-dimer (D-dimer) were observed. However, there were no statistical differences between the two groups. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 9 publications
2
33
0
Order By: Relevance
“…Severe pre-eclampsia was found to be associated higher levels of CRP than mild preeclampsia in line with previous studies. Kabayashi et al 27 reported that D-Dimer levels and changes of platelet counts are useful predictive markers with optimal time for the termination of pregnancy in patients with severe pre-eclampsia. 7 Mother delivering at term had circulating PCT concentrations similar to those observed in the apparently healthy adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Severe pre-eclampsia was found to be associated higher levels of CRP than mild preeclampsia in line with previous studies. Kabayashi et al 27 reported that D-Dimer levels and changes of platelet counts are useful predictive markers with optimal time for the termination of pregnancy in patients with severe pre-eclampsia. 7 Mother delivering at term had circulating PCT concentrations similar to those observed in the apparently healthy adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin activation can also lead to deposition of fibrin in multiple organ systems, which is a major contributor to the pathology of pre-eclampsia. 2 Excessive thrombin generation can be assessed by measuring the concentration of thrombin–antithrombin complexes, 138 antithrombin III activity 139 or by a thrombin generation assay. 140 In some patients, pre-eclampsia and/or HELLP syndrome can be considered as thrombotic microangiopathy-like disorders, in light of the similarities in clinical presentation and pathology observed in multiple organs (thrombocytopenia, haemolysis, endothelial injury, complement activation and deposition of thrombin and/or fibrin in arterioles and capillaries of the brain, kidneys and liver).…”
Section: Pathogenetic Mechanismsmentioning
confidence: 99%
“…A wide variety of hemostatic disturbances have been described in pre‐eclampsia. They include thrombocytopenia as well as consumption of coagulation factors and inhibitors [2–5], with evidence of thrombin generation [3–5] and inhibited fibrinolysis [5–7]. However, the changes in the circulating levels of tissue factor pathway inhibitor (TFPI) in pre‐eclampsia need to be clarified.…”
Section: Introductionmentioning
confidence: 99%